Homo homini homo. Tre caverne: relazione e schermo - Heritier, Paolo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
The article set up the relationship between the three caves of Lon Fuller’s speluncean explorers’ case, Plato’s cave myth in Carbone’s reading, the new digital/ VR 360° “cave”. Other metaphorical or real caves (from those painted by prehistoric man to the concentration camp cave described by Levi) open the possibility of a theory inspired by the ideal of homo homini homo, in its opposition to the theological-political models of homo homini lupus and homo homini deus. What emerges is a possible an-thropological theory of the foundation of social bonding and law based on a reconfigu-ration of the idea of sacrifice.